2010
DOI: 10.1371/journal.pone.0014061
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms for Heterogeneity in Leprosy Susceptibility Can Explain Disease Clustering within Households

Abstract: The epidemiology of leprosy is characterized by heterogeneity in susceptibility and clustering of disease within households. We aim to assess the extent to which different mechanisms for heterogeneity in leprosy susceptibility can explain household clustering as observed in a large study among contacts of leprosy patients.We used a microsimulation model, parameterizing it with data from over 20,000 contacts of leprosy patients in Bangladesh. We simulated six mechanisms producing heterogeneity in susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 27 publications
1
70
0
1
Order By: Relevance
“…We compared the results based on different hypothesized mechanisms for susceptibility, because each of these mechanisms could be valid [9]. The quantitative results were sensitive to the mechanism chosen.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the results based on different hypothesized mechanisms for susceptibility, because each of these mechanisms could be valid [9]. The quantitative results were sensitive to the mechanism chosen.…”
Section: Discussionmentioning
confidence: 99%
“…The high concentration of new cases among household contacts of leprosy patients has been demonstrated in numerous international studies (Fischer et al 2010, Sales et al 2011. Brazilian studies have also highlighted the elevated risk factors associated with these close contacts (Goulart et al 2008, Sales et al 2011.…”
mentioning
confidence: 92%
“…Using computer modelling techniques (SIMCOLEP) to study a cohort of contacts in Bangladesh, Fischer et al (2010) concluded that there is heterogeneity in contact susceptibility and that the household contact him/herself is a significant factor independent of other susceptibilities.…”
mentioning
confidence: 99%
“…Briefly, individuals are divided into 3 categories: resistant ( R , with probability q S = 1-p s ), susceptible to paucibacillary infection (S P , with probability p s *p p ), and susceptible to multibacillary infection (S M , with probability p s *q p where q P = 1-p p ). Resistance, q s , is meant to convey both genetic resistance and socioeconomic protective factors [13,18]. Resistance to multibacillary infection, p p , is meant to convey genetic resistance [18]; this value is higher than the observed proportion of new cases that are PB (0.8 vs. 0.54), but the discrepancy is explained by the high rate of self-cure among PB cases ( α PN ).…”
Section: Methodsmentioning
confidence: 99%